Estimation of the resistance of maize lines to Sphacelotheca reiliana in the northern Steppe of Ukraine - V. Y. Cherchel; O. F. Stasiv; T. M. Satarova; O. V. Zatyshniak; E. V. Lazarev (Agrology, 2020)
Maize selection for disease resistance is an actual task owing to the expansion of phytopathogens under climate changes and maize production in monoculture. The aim of the research was to differentiate modern maize initial breeding material by susceptibility to causative agent of head smut (Sphacelotheca reiliana) in the conditions of the northern Steppe of Ukraine. 28 maize inbreds from the collection of SE The Institute of Grain Crops of NAAS were taken for estimation of resistance to head smut in contrasting 2018 and 2019 on artificial infectious background in Dnipropetrovsk region. According to the results of the cultivation, all tested samples were divided into four classes on the level of susceptibility to disease: stable, low sensitive, middle sensitive and unstable. In 2018, 11 lines showed low sensitivity, 8 lines – middle and 9 lines – high sensitivity to head smut. In 2019 – no signs of pathogenesis were detected in 12 lines while 6 inbreds were classified as low sensitive, 7 – middle sensitive and 3 – high sensitive. The largest amount of stable or low sensitive to S. reiliana lines was among those ones originated from Lancaster germplasm. Among 9 lines of Iodent germplasm in 2018‒2019 inbred DK 742 was assigned to the 2nd class of sensitivity; DK315 and DK744 in 2018 – to 4th and 3rd classes while in 2019 – to 2nd and 1st classes, respectively. Five other Iodent lines were either unstable or had intermediate susceptibility to the pathogen. As to Reid germplasm in two research years DK239MV showed the sensitivity of 1.6‒9.0% and was classified as low sensitive; DK2323 was determined as intermediate sensitive in 2018 and high sensitive in 2019. In arid conditions of 2018 up to 20% of DK367 plants had typical signs of infection while in wet 2019 this line had no signs of infection by S. reiliana at all. Flint inbred DK4538 appeared unstable in both years. Other inbreds with flint grain type DK959 and DK276 in two years varied greatly on their resistance. DK 247MV which was related to line Co125 had low susceptibility to the pathogen at the level of 4.7‒5.6%. DK129-4, also related to Co125, demonstrated susceptibility from 0 to 18.3%. Since maize resistance to head smut is a polygenic trait, it largely depends on weather conditions, as well as the virulence of the pathogen, the ability of plants to prevent pathological processes at the level of histogenesis, fungistatic effects of soil microorganisms and maize root secretions. Taking into account the influence of the external environment, the revealed perspective lines with ability to withstand the head smut in the northern Steppe of Ukraine can be used in the selection process of maize hybrids resistant to S. reiliana